Practical pentesting - Lowrie, Daniel; Stine, Brad (Packt Publishing, 2024)
The course begins by introducing the fundamentals of penetration testing, distinguishing the roles of pentesters - the good, the essential, and the challenges they face. It lays the groundwork with pre-engagement essentials, including data security agreements and crafting a detailed Statement of Work (SOW), ensuring clarity and legal safeguarding before any testing begins. The course focuses on the pentesting methodology, guiding you through the stages of assessment from validating scope to reconnaissance, vulnerability scanning, and exploitation. It emphasizes the importance of maintaining access, covering tracks, and preparing comprehensive deliverables to ensure actionable insights for enhancing security. The course wraps up by exploring personal engagement toolkits and pentesting platforms, providing practical knowledge for effective pentesting. It also touches upon blue team pentesting, highlighting the collaborative effort required in cybersecurity to protect against threats. What you will learn Plan and execute effective penetration tests Perform detailed reconnaissance and vulnerability scans Exploit vulnerabilities to assess security posture Maintain unauthorized access discreetly Execute strategies to conceal testing activities Produce comprehensive security assessment reports Audience This course is ideal for IT professionals, cybersecurity enthusiasts, and ethical hackers seeking to enhance their pentesting skills. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Daniel Lowrie: Daniel Lowrie's IT career began with workstation support and Y2K compliance updates for a teaching hospital in North-Central Florida. His journey led him to become an in-classroom trainer and Mentored Learning Instructor, specializing in courses covering Microsoft Windows Desktops and Servers, Active Directory, Networking, CCNA, and Linux. He then transitioned to becoming a Systems and Network administrator for a large insurance company before joining ACI Learning as an Edutainer. Certifications: CompTIA A+, Network+, Linux+, CySA+, and PenTest+; CEH; MCSA; CFR; eJPT Brad Stine: Brad Stine is the Chief Information Security Officer at Semper Sec with years of experience in security architecture. Throughout his career, Brad has played a key role in the development and delivery of technology-driven business solutions, including projects centered around cloud transformation, CI pipeline automation, and identity access management. Brad is highly skilled in Analytics, Incident Management, Vulnerability Management, ISO 27001:2013, and Enterprise Architecture. He has an extremely knowledgeable computer science background and holds a CISSP certification.
Online resource; title from title details screen (O'Reilly, viewed February 27, 2024)
Keywords: Penetration testing (Computer security); Tests d'intrusion; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet